2023
DOI: 10.1039/d3sc00500c
|View full text |Cite
|
Sign up to set email alerts
|

In vivo biocompatibility of ZIF-8 for slow release via intranasal administration

Abstract: Studying the toxicity of zeolitic imidazolate framework-8 (ZIF-8) in context of intranasal administration will help researchers in building depot platforms for this non-invasive route of delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…More recently, Kumari et al demonstrated how coating liposomes in ZIF and delivering them intranasally into mice can extend the bioresidency half-life of the liposomes by over four times. 171 Further, they were able to deliver up to 1 mg of uncoated ZIF-8 directly into the intranasal cavity and observed no tissue damage to the delicate turbinate structures in the sinuses, nor loss of pulmonary function or elevation of liver and kidney enzymes, showing this route as being highly compatible with MOF delivery. These efforts�although nascent and still in the stage of fundamental discovery� show potential for the possible marriage of all aforementioned benefits of MOFs as vaccine carriers along with being able to exploit them as a tool for mucosal delivery.…”
Section: Needle-free Deliverymentioning
confidence: 92%
See 1 more Smart Citation
“…More recently, Kumari et al demonstrated how coating liposomes in ZIF and delivering them intranasally into mice can extend the bioresidency half-life of the liposomes by over four times. 171 Further, they were able to deliver up to 1 mg of uncoated ZIF-8 directly into the intranasal cavity and observed no tissue damage to the delicate turbinate structures in the sinuses, nor loss of pulmonary function or elevation of liver and kidney enzymes, showing this route as being highly compatible with MOF delivery. These efforts�although nascent and still in the stage of fundamental discovery� show potential for the possible marriage of all aforementioned benefits of MOFs as vaccine carriers along with being able to exploit them as a tool for mucosal delivery.…”
Section: Needle-free Deliverymentioning
confidence: 92%
“…These results were impressive as they were able to deliver up to 8 mg into the lungs and, according to histopathological analyses, without damaging the tissues. More recently, Kumari et al demonstrated how coating liposomes in ZIF and delivering them intranasally into mice can extend the bioresidency half-life of the liposomes by over four times . Further, they were able to deliver up to 1 mg of uncoated ZIF-8 directly into the intranasal cavity and observed no tissue damage to the delicate turbinate structures in the sinuses, nor loss of pulmonary function or elevation of liver and kidney enzymes, showing this route as being highly compatible with MOF delivery.…”
Section: Advantages Of Using Mofs/cofs To Fill the Gap In Current Vac...mentioning
confidence: 99%
“…The high extent of 20 nm NPs' structural degradation upon exposure to DIFP down to ultrasmall 7 nm NPs should be considered beneficial to avoid NP bioaccumulation facilitating their body clearance. 23 The size dependence of ZIF structural degradation is also reflected in the high linker release with [mIm] reaching 0.05 M for the nanometer-sized particles (Table S3). ZIF Nerve Agent Detoxification: Dual P−F Bond Breakdown and AChE Reactivation.…”
Section: ■ Experimental Sectionmentioning
confidence: 98%
“…It is noteworthy that the structural degradation is advantageous since it prevents the accumulation of nanoparticles (NPs) in the body . Indeed, in vivo biosafety of ZIF-8 NPs and degradation products thereof has been recently demonstrated …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation